2020
DOI: 10.1088/1361-665x/abb575
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetorheological elastomer-based adaptive tuned vibration absorber: design, analysis and experimental characterization

Abstract: The present study aims at the development of a novel semi-active adaptive tuned vibration absorber (SATVA) capable of tuning its natural frequency adaptively in low frequency range. The absorber consists of a multilayer sandwich beam featuring magnetorheological elastomer (MRE) and integrated U-shaped electromagnets which are attached at the top and bottom layers of the sandwich beam. Electromagnets are designed to provide the required magnetic field to alter the stiffness of the MRE layers while also acting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…[ 107 ] In regard to their shape, typical shear testing of mechanical properties requires circular or cylindrical shape, and those are the most prevalent in the literature. [ 108–110 ] However, one of the most useful characteristics of MREs is that, since they are fabricated from a fluid elastomer that solidifies during the curing process, they can adopt other sizes and shapes. Thus, cubic, [ 111 ] rectangular, [ 93 ] or even coaxial micropumps have been developed.…”
Section: Materials Processing and Functional Responsementioning
confidence: 99%
See 1 more Smart Citation
“…[ 107 ] In regard to their shape, typical shear testing of mechanical properties requires circular or cylindrical shape, and those are the most prevalent in the literature. [ 108–110 ] However, one of the most useful characteristics of MREs is that, since they are fabricated from a fluid elastomer that solidifies during the curing process, they can adopt other sizes and shapes. Thus, cubic, [ 111 ] rectangular, [ 93 ] or even coaxial micropumps have been developed.…”
Section: Materials Processing and Functional Responsementioning
confidence: 99%
“…Following this argument, a semiactive ATVA has been developed, consisting of a five‐layered sandwich beam treated with two layers of isotropic MREs with 25 vol% CI particle fractions. [ 109 ] The behavior of the MRE was modeled using finite elements. To verify the appropriate functioning of the system, the vibration absorber was excited with a sinusoidal harmonic vibration signal under a constant acceleration of 0.1 m s −2 in the range of 2 to 20 Hz and sandwiched between two electromagnets excited with different currents (0, 2, 4, and 6 A) to generate the magnetic field.…”
Section: Applications Of Mr Elastomersmentioning
confidence: 99%
“…It has been unanimously reported that the shear moduli of MREs increase with increasing magnetic field strength. Owing to their field-dependent modulus, contactless control, and the shape-morphing features, MREs have attracted much attention over the past few years, making them an ideal smart material candidates to address stiffness or modulus tunability requirements in different engineering applications such as smart sensors and actuators, adaptive vibration isolators, [25][26][27][28] tunable vibration absorbers (TVAs), [29][30][31][32][33] adaptive dampers, [34][35][36] sandwich beams, [37][38][39][40] and biomedical engineering such as tissue engineering [41][42][43][44] and drug delivery. [45,46] There have also been several review papers in the literature that discuss the potential applications of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve this problem, MR elastomer is utilized in the flexible beam. Particle chains are locked into the viscoelastic matrix with variable stiffness (Rasooli et al, 2020). The corresponding natural frequency of a developed vibration absorber with MR elastomer was tuned from 55 to 82 Hz with an increase of 47% (Deng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%